Recent findings on drug hypersensitivity in children - Felix, Mara Morelo Rocha; Kuschnir, Fábio Chigres; Boechat, José Laerte; Castells, Mariana (Frontiers in Allergy, 2024)
Drug hypersensitivity reactions (DHR) in children have a significant impact on clinical practice and public health. Both under-diagnosis (due to under-reporting) and over-diagnosis (due to the overuse of the term “allergy”) are potential issues. The aim of this narrative review is to describe the most recent findings of DHR in children/adolescents and gaps regarding epidemiology, antibiotic allergy, antiepileptic hypersensitivity, vaccine allergy, and severe cutaneous adverse reactions (SCAR) in this age group.